Compassion: a Phenomenology of the Affective Experience - Bleizgienė, Ramunė (Literatūra, 2024)
The article, based on a phenomenological approach to feelings, aims to describe the peculiarities of the experience of one emotion – compassion – on the basis of wedding songs and related wedding customs. Compassion was one of the ‘qualifications’ that the young woman had to prove at the wedding, that is, the initiation of women into the adult world. The similarity between the funeral and the wedding lament shows that compassion not only helped the young woman to experience a fundamental transformation in her life, but also allowed her to establish a connection with the sacred world of the dead. One of the social functions of compassion was the creation of an emotional relationship with the new family. Only by changing the hearts of the members of the new family from cold to compassionate could the young woman become a member of the new family. The article shows that this feeling is important in understanding the peculiarity of interpersonal relations, the value attitudes and behavioural patterns that justify them and are expressed in them. The experience of compassion at the wedding brought the family and the whole community together, justified and expressed the fundamental value attitude that binds individuals together and justifies their behaviour, which is being present, as well as acting in relation to those around them.
Keywords: phenomenology; affectivity; intersubjectivity; intercorporeality; living world; Žemaitė; compassion; wedding songs; lament